Intraoral Approach Drainage of Submasseteric Abscess in a 14-Month-Old Child - Mohamad Umbaik, Norsyamira Aida; Hafizzi, Nik Syahrul; Nik Mohamad, Nik Khairani; Ismail, Hashimah; Mohamad, Irfan (International Journal of Human and Health Sciences (IJHHS), 2019)
Submassteric abscess is a rare head and neck abscess. It may mimic a parotid abscess due to very close anatomical relationship. We present a 14-month-old child presented with fever, poor oral intake, irritability, and left-sided cheek swelling. Contrast-enhanced computed tomography of the neck showed an abscess formation in left submasseteric space. Intraoral drainage of abscess was successfully performed under general anesthesia. Patient recovered well and was discharged on day three post operatively. Subsequent follow up at one-week post operatively showed no recollection of the abscess. International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 123-125